Demoras na assistência obstétrica de gestantes com desfecho de óbito fetal (ante ou intraparto): estudo de caso-controle - Martins, Marley Carvalho Feitosa (2018)
Objective: To evaluate the association between delays in the care provided to pregnant women seeking obstetric care and the fetal death outcome in a tertiary reference maternity. Methods: Observational study, Case-Control type analytical, including 72 cases of fetal deaths and 144 controls (live births) of women admitted to the obstetrics service at Maternidade Escola Assis Chateaubriand (MEAC), in Fortaleza, Ceará, from January to November 2017. The controls were matched (2: 1) by gestational age and municipality of approximate origin to cases. The groups were compared regarding the model of the three delays in obstetric care. The Pearson's Chi-square test and the Fisher's exact test were used to compare the groups. It was considered at p <0.05 as significant. Results: There was no statistical difference between the groups regarding socioeconomic variables. The fetal death group had a lower number of prenatal consultations (>6 appointment: 27,8%x 40,3%, p=0,003), less rating at gestation of risk (41,7%x 55,9%, p=0,048), less guidance about place of birth (44,5%x64%, p=0,009), lower cesarean frequency (25,4%x 65,7%) and higher prevalence of hemorrhagic syndromes (33,3%x 19,4%, p=0,024) and syphilis (15,3%x 4,2%, p=0,004). In the bivariate analysis, all delays, except difficulty with transportation and geographical difficulty were statistically different between groups. In logistic regression, the variables that persisted significantly associated with fetal death were: Refusal of Care (OR=10,7; CI95%: 1,92-59,6), delay in diagnosis (OR=22,2; CI95%: 4,41-112,3) and inadequate conduct with the patient (OR=4,56; CI95%: 1,08-19,2). Conclusion: The invisibility given to fetal deaths at the various levels of attention has as a consequence the delays in seeking care by the pregnant woman, as well as the "normalization" of the complaints and determining complications for the outcome of death. More investments are needed and attention to fetal deaths as a direct measure of access and quality of care in the maternal and child care network.